Cancer du colon - BACHIR, WAFA; GOTTECHE, NABILA (My University, 2020)
Lifestyle and genetic predisposition are identified as risk factors for CRC. The better understanding of colorectal carcinogenesis and tumor biology now allows the definition of specific biological profiles of CRC based on the ranking that the most common in the world in humans and its incidence is increasing every year. It is a disease involving several environmental factors; genetic; individual; smoking; Alcohol. The objective of our study was to describe the epidemiological and anastomhistopathological profile of colorectal cancer in the wilayaMostaganem.A study was carried out on 57 female and male patients in favor of men accompanied by a dominance of colon cancer over cancer rectal as well as a very high frequency of well differentiated adenocarcinoma. The pathological study allowed us to become involved in the diagnostic work of colorectal cancer and the characteristics of the three types of colorectal cancer chosen in this study have already been reported and described in the literature.
Keywords: adenocarcinoma.colorectal cancer; carcinogénesis.